UNDANG-UNDANG LARANGAN PRAKTIK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT SEBAGAI FAKTOR INTEGRASI DI BIDANG KEGIATAN USAHA - Yanuarsi, Susi (Faculty of Law, University of Palembang, 2018)
The law that represents socially agreed upon is to regulate justice in society. As a social institution, the organization that is responsible for the needs of the community must implement it. Therefore a community will hold it in a way that is different from other communities